Enhanced efficiency of generating human-induced pluripotent stem cells using Lin28-30Kc19 fusion protein - Son, Boram; Yoon, Hyungro; Ryu, Jina; Lee, Haein; Joo, Jinmyoung; Park, Hee Ho; Park, Tai Hyun (Frontiers in Bioengineering and Biotechnology, 2022)
Induced pluripotent stem cells (iPSCs) have intrinsic properties, such as self-renewal ability and pluripotency, which are also shown in embryonic stem cells (ESCs). Challenge for improving the iPSC generation efficiency has been an important issue and there have been many attempts to develop the iPSC generation methods. In this research, we added Lin28, known as one of the reprogramming factors, in the form of soluble recombinant protein from E. coli to improve the efficiency of human iPSC (hiPSC) generation, in respect of alkaline phosphatase(AP)-positive colonies. To deliver Lin28 inside the cells, we generated soluble Lin28-30Kc19 fusion protein, with 30Kc19 at the C-terminal domain of Lin28. 30Kc19, a silkworm hemolymph-derived protein, was fused due to its cell-penetrating and protein-stabilizing properties. The Lin28-30Kc19 was treated to human dermal fibroblasts (HDFs), in combination with 4 defined reprogramming factors (Oct4, Sox2, c-Myc and Klf4). After 14 days of cell culture, we confirmed the generated hiPSCs through AP staining. According to the results, the addition of Lin28-30Kc19 increased the number and size of generated AP-positive hiPSC colonies. Through this research, we anticipate that this recombinant protein would be a valuable material for increasing the efficiency of hiPSC generation and for enhancing the possibility as a substitute of the conventional method.